A tantalum oxide-based core/shell nanoparticle for triple-modality image-guided chemo-thermal synergetic therapy of esophageal carcinoma. (1st July 2017) - Jin, Yushen; Ma, Xibo; Zhang, Shuai; Meng, Hui; Xu, Min; Yang, Xin; Xu, Wanhai; Tian, Jie
Abstract: Early detection and therapy of esophageal cancer is very important for improving the prognosis and survival rate of the patient. A theranostic agent that combines multimodal imaging with cancer therapy may be used for augmenting the visualization and treatment of the cancer. Herein, we report the synthesis of a hollow tantalum oxide (TaOx ) nanoparticle that was successfully engineered by encapsulation of polypyrrole (PPy) and doxorubicin (DOX) in the core and conjugation with a near infrared fluorescence dye (NIRDye800) on the shell of the hollow TaOx nanoparticles. The as-prepared core/shell nanoparticles showed multimodal imaging features including computed tomography (CT) (for the preliminary location of the tumor), photoacoustic (for the anatomical localization of the tumor), and fluorescence imaging (for real-time monitoring of the tumor margin) and pH- and thermal-sensitive drug release. Because the early esophageal carcinoma is a type of superficial cancer, a subcutaneous model in the thigh was used for the in vivo study. The core/shell nanoparticles shows high imaging contrast between the tumor and the adjacent tissues and controllable photothermal therapy (PTT) and chemotherapy. Our results indicated that the obtained core/shell nanoparticles had significant potential in the triple-modality imaging guided precisely chemo-thermal synergetic therapy of esophageal cancer. In addition, after aerosol administration, our nanoparticles also exhibited comparable therapeutic efficacy with the intravenous administration, which is more suitable for clinical therapy of esophageal carcinoma. Highlights: A core/shell nanoparticle was prepared for triple-modality image guided chemo-thermal therapy of esophageal carcinoma. Tumors were located using CT and photoacoustic imaging and tumor margin were real-time monitored by fluorescence imaging. Due to drug release was pH/thermal-sensitive, the nanoparticles can used for locally controlled cancer therapy. The chemo-thermal synergetic therapy of esophageal carcinoma significantly improved the therapeutic efficiency.